Holding the baby: early mother-infant contact after childbirth and outcomes. - Redshaw, M; Hennegan, J; Kruske, S (2014)
AIM: to describe the timing, type and duration of initial infant contact and associated demographic and clinical factors in addition to investigating the impact of early contact on breastfeeding and maternal health and well being after birth. METHOD: data from a recent population survey of women birthing in Queensland, Australia were used to describe the nature of the first hold and associated demographic characteristics. Initial comparisons, with subsequent adjustment for type of birthing facility and mode of childbirth, were used to assess associations between timing, type and duration of initial contact and outcomes. Further analyses were conducted to investigate a dose-response relationship between duration of first contact and outcomes. FINDINGS: women who had an unassisted vaginal birth held their infant sooner, and for longer than women who had an assisted vaginal birth or caesarean and were more satisfied with their early contact. Multivariate models showed a number of demographic and clinical interventions contributing to timing, duration and type of first contact with type of birthing facility (public/private), area of residence, and assisted birth as prominent factors. For women who had a vaginal birth; early, skin-to-skin, and longer duration of initial contact were associated with high rates of breastfeeding initiation and breastfeeding at discharge, but not breastfeeding at 13 weeks. Some aspects of early contact were associated with improved maternal well being. However, these associations were not found for women who had a caesarean birth. With longer durations of first contact, a dose-response effect was found for breastfeeding. CONCLUSION: results of the study provide a description of current practice in Queensland, Australia and factors impacting on early contact. For vaginal births, findings add to the evidence in support of early skin-to-skin contact for an extended period. It is suggested that all research in this area should consider the effects of early contact separately for women having vaginal and caesarean births. IMPLICATIONS FOR PRACTICE: care providers should consider extending the period of early contact in routine care following vaginal birth and explore the way in which women having a caesarean birth might be better supported in benefitting from early contact with their infant.